At play in the master's workshop: the experience of reading in the novels of Henry James - Seddon, Deborah Ann (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1998)
James's belief that "it is art that makes life" is essential to his own literary technique and to the reading experience within and in relation to his novels. The thesis seeks to posit the notion of reading as a fundamental concern in Henry James's fiction. Drawing largely on the phenomenological and anthropological approaches to the reading process of Wolfgang Iser, this thesis examines the Jamesian text as a performative event involving author, reader and character in creative and interpretative narrational struggles. Iser uses "play" as an integral term to describe the dynamic between author-reader-text which produces a literary work of art. In James's fiction the doubling of the author/reader and reader/character role within the text crucially structures a narrative form which is itself an inquiry into the human use of fiction. The Iserian conception of the act of reading as an engagement with the "gaps" within the play-space of the literary text can elucidate James's structural and thematic use of such sites of indeterminacy to foreground the enlivening necessity of an indeterminate "felt life" within human narrative structures. What Maisie Knew highlights the most important rule in the game -- the necessity for the reader to create meaning from the indeterminate aspects of the text. The shared exercise for author-reader-character is the attempt to access the child's unformulated inner reality to ascertain what Maisie knows. In the section on The Portrait of a Lady Iser's notion of reading as an ideational activity aids an inquiry into the human use of mental fictive picturing to compose reality. The Ambassadors demonstrates the "anthropological" need for the particular mode of consciousness brought about by the literary text when we engage in a world as real as but different to our own. Strether is the reader's ambassador in this world and his interpretative activity mirrors the reader's quest. In The Golden Bowl the bewildering multiplicity of readings made possible by the indeterminate aspects of the literary text instigates a contest for narrative forms in which the chosen fictions of the readers/characters must be actively willed into existence.
Keywords: James, Henry, 1843-1916 -- Criticism and interpretation